Penggunaan Media Pembelajaran Flashcard Dalam Meningkatkan Kemampuan Membaca Siswa Kelas 1 SD Negeri Tegalrejo III - Annisa Nur Aena; Heru Purnomo (Pendagogia: Jurnal Pendidikan Dasar, 2025)
This type of research is Classroom Action Research (CAR) which aims to improve students' reading skills by implementing flashcard media. The subjects of this study were 28 first-grade students of Tegalrejo 3 Elementary School and teachers. Data collection methods in this study include observation, interviews, documentation, and tests. Based on the results of the study, students' reading skills increased after the implementation of cycle I and II activities compared to the pre-cycle period. The findings of the study indicate that first-grade students at Tegalrejo 3 Elementary School became more proficient in reading, especially after using flashcard learning media in cycles I and II.